VD_FINDINFO Arrêt / 2015 / 895 vom 17. November 2015 - VD Tribunal cantonal (2015)
AIASSURANCE, INFIRMITÉ CONGÉNITALE, RÉPARTITION DES FRAIS | 13 al. 1 LAI, 13 LAI, 3 al. 2 LPGA, 3 LPGA, 59 LPGA, 1 OIC, 2 OIC